Perancangan Ulang Tata Letak Fasilitas Produksi pada Pabrik Tahu RR dengan Mempertimbangkan Kondisi Eksisting dan Alur Proses Produksi - Kafilany, Siti Marina; Siregar, Mulki; Cahyono, Cahyono; Wiwin, Wiwin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The inefficient layout of production facilities can hinder smooth production processes and reduce operational effectiveness. The RR Tofu Factory still uses a traditional, unstructured layout that does not comply with the principles of facility layout design (FLA). This study aims to redesign the layout of the production facilities of the tofu factory to improve operational efficiency and space utilization. This study employs a descriptive quantitative method involving field data collection and analysis of equipment quantities, processing times, and area requirements. The results of the study show that the new layout design can organize departments more systematically, streamline the production flow, and reduce process obstacles. With this redesign, the RR Tofu Factory is expected to operate more effectively and in compliance with facility layout standards